Force & motion - Lafferty, Peter; Streeter, Clive (New York : DK, 2000)
Explores the principles of force and motion, describing how they have been applied from ancient to modern times.
Includes index.
Wilson's Junior High School.
7.7.
7.7
5-8
Keywords: Force and energy -- Juvenile literature; Motion -- Juvenile literature; Force and energy; Motion; Force and energy; Motion